Evaluating The Effectiveness Of Telemedicine In Managing Chronic Diseases In Pediatric Patients (The Review of Diabetic Studies, 2025)
Background: Chronic diseases in pediatric patients, such as asthma, diabetes, and congenital heart conditions, require continuous monitoring and frequent consultations. Traditional in-person care faces challenges including geographic barriers and logistical burdens. Telemedicine offers a potential solution by enabling remote care delivery through digital tools, though its effectiveness in pediatric chronic disease management requires comprehensive evaluation.Methods: This study employed a mixed-methods, descriptive cross-sectional design. A total of 150 pediatric patients (aged 5–18 years) with chronic diseases and their caregivers were recruited via purposive sampling. Data were collected using structured questionnaires, clinical records, and semi-structured interviews. Quantitative data were analyzed with descriptive and inferential statistics (paired t-tests, chi-square tests), while qualitative interview data were analyzed thematically to assess clinical outcomes, treatment adherence, caregiver/patient satisfaction, and user experiences.Results: The majority of participants were adolescents (43.4% aged 13–18). Video consultation was the most used service (80%). High treatment adherence was reported in 56.7% of patients. Clinical outcomes showed significant improvements: asthma control scores increased by 23.5%, average blood glucose levels decreased by 17.2%, and hospitalization frequency was reduced by 60%. Satisfaction levels were high, with 86.7% of caregivers and patients reporting being satisfied or very satisfied.Conclusion: Telemedicine is an effective and well-accepted modality for managing chronic diseases in pediatric patients, leading to improved clinical outcomes, enhanced treatment adherence, reduced hospitalizations, and high satisfaction. It should be integrated as a complementary tool within pediatric chronic care models to support accessible, continuous, and patient-centered healthcare delivery.